Spatial Variations of Phytoplankton Biomass Controlled by River Plume Dynamics Over the Lower Changjiang Estuary and Adjacent Shelf Based on High-Resolution Observations - Zhang, Zhaoru; Zhou, Meng; Zhong, Yisen; Zhang, Guosen; Jiang, Shan; Gao, Yonghui; Zhang, Ruifeng; Smith, Walker O. (Frontiers in Marine Science, 2020)
Phytoplankton biomass in estuarine and continental shelf regions are regulated and modified by physical processes, but these interactions have mostly been investigated at a scale of tens of kilometers, and the role of meso- to sub-mesoscale dynamical processes of freshwater plumes in regulating the spatial and temporal variations of algal biomass is largely unknown. To assess the importance of features at these scales, high-resolution (horizontal spacing smaller than 1 km) cross-sectional profiles of hydrographic and biogeochemical variables were collected in the lower Changjiang Estuary and adjacent continental shelf with a towed, undulating vehicle equipped with sensors measuring fluorescence, turbidity and irradiance. Discrete stations were also occupied to allow for the characterization of nutrients. Multiple physical features at different scales regulated the spatial variation of phytoplankton biomass. Phytoplankton biomass was initialized by an improved irradiance field driven by reduced turbidity together with a rapid development of subsurface stratification at the main plume front (isohaline of 23) downstream from the turbidity maximum zone. Phytoplankton blooms did not occur until outcrops located within the main front that were characterized by surface convergence and downwelling, which contributed to large algal biomass by mass trapping and enhanced light penetration. Wave-like features were detected seaward of the main front, coinciding with deacceleration of currents, indicating that they are front-released internal waves that increase algal retention time. This study revealed the critical role of small-scale processes near the plume front in triggering phytoplankton blooms under the large-scale context of improved light conditions, coastal upwelling and nutrient additions from intruding oceanic waters.